Implementasi Strategi Karakter Nasionalisme pada Peserta Didik UPT SD Negeri 6 Gresik - Sari, Putri Dwi Kartika; Alfiansyah, Iqnatia (EduInovasi: Journal of Basic Educational Studies, 2024)
This research tries to show how the science discipline encourages the development of nationalistic views. This research uses qualitative research methodology and descriptive methodology. Observations, interviews, and documentation are used to collect data that has not yet been collected. This research was carried out at UPT SD Negeri 6 Gresik. The aim of this research is the introduction of nationalistic sentiments through scientific classes, with the class teacher and school principal serving as facilitators. The data analysis stages used include data reduction, data presentation, and conclusions or verification. The results of the research show that the application of nationalistic character in scientific subjects in class IV UPT SD Negeri 6 Gresik includes habituation, exemplary/modeling activities, and other learning activities. Apart from that, there are circumstances that support and hinder the implementation of nationalism. The supporting aspect is in the form of appropriate infrastructure so that the use of learning media can facilitate the realization of a Nationalist character. Meanwhile, it is a challenge for students to understand the nature of nationalism. Therefore, class teachers and school principals use simple language to explain the character of nationalism.